Curriculum and instruction: pedagogical approaches to teaching and learning with Twitter in higher education. Issue 1 (29th July 2019) - Gleason, Benjamin; Manca, Stefania
Abstract : Purpose: While the ubiquity of social media as a mode of communication, collaboration, connection and creativity has been widely adopted in journalism, entertainment, healthcare and others, the field of education has been more reticent to integrate social media for teaching and learning purposes. This paper aims to summarize research on how social media may support educational aims with specific reference to large classrooms. In addition, the authors provide practical tips on using Twitter from the experience teaching in a typical higher education setting: a large, undergraduate course in a public university. Finally, the authors offer conclusions about how instructors can use social media to support increased engagement, professional development and digital literacy skills. Design/methodology/approach: This paper presents a real-life "case study" of using Twitter in an educational context common to many in higher education: a large, undergraduate lecture class over the course of one semester. This course focused on the foundations of educational technology and was a requirement of receiving a teaching credential at a large public institution in the Midwest. As a required course, students from a number of different majors were enrolled in the course, including biology, chemistry, mathematics, English, history, world languages, physical education and many more. While these majors were grouped by content-area groups (Science, Technology, Engineering, and Math; the humanities; and physical education), for this paper the authors will focus on the part of the course where students were all together in lecture format. Guided by the research above, and pedagogical practices discussed elsewhere (Greenhow and Gleason, 2012 ), it was decided to use Twitter for a number of different pedagogical purposes, including in-class discussion, increase student engagement with course material, expand student interaction and develop student presence. Findings: The use of Twitter was found to increase student participation, help facilitate conceptual understanding, to foster students' "social presence, " and to increase interactions with "real world experts." Twitter provided a way, for example, for students in a large lecture course to participate, and roughly 90 per cent of students did so with Twitter. Likewise, instructors used Twitter as a way to bridge learning across different experiences (i.e. lab activities, lecture and online lesson), while also providing a way to support social presence (letting students share humorous pictures). Finally, Twitter facilitated interaction with content experts including historians, during a lesson on global collaboration. Research limitations/implications: Overall, integrating Twitter into a large, lecture course seemed to suggest a number of positive learning outcomes, including presenting opportunities for student voice and expression, visible participation, the development of social presence and tools to connect different course activities (e.g. lecture, in-class activities and lab activities). For example, much research in this field has begun to explore the educational outcomes associated with social media use, and this study contributes to this emerging field. Here, the authors advocate for using social media to support interactive, collaborative and social learning.